Surds and Indices
- √56 + √56 + √56 + .... ) ÷ 22 = ?
-
View Hint View Answer Discuss in Forum
Here, Let us Assume ,
p = √56 + √56 + √56 + ...........
⇒ p = √56 + p
Square on both side and solve the above equation.Correct Option: C
Here, Let us Assume ,
p = √56 + √56 + √56 + ...........
⇒ p = √56 + p
Square on both side and solve the above equation.
⇒ p2= 56 + p
⇒ p2 - p= 56
⇒ p(p - 1 ) = 56
⇒ p(p - 1 ) = 8 x 7
⇒ Either p = 8 or p - 1 = 7
⇒ So p = 8;
Now given equation in question is
√56 + √56 + √56 + .... ) ÷ 22 = ?
⇒ p ÷ 22 = ?
Put the value of p
⇒ 8 ÷ 22 = ?
⇒ 8 ÷ 4 = ?
⇒ ? = 2;
- Find the value of m - n, if ( 9n x 32 x (3-n/2)-2 - (27)n ) / ( 33m x 23 ) = 1/27 ?
-
View Hint View Answer Discuss in Forum
( 9n x 32 x (3-n/2)-2 - (27)n ) / ( 33m x 23 ) = 1/27
Apply the law of Fractional Exponents and Laws of Exponents
(am)n = am x n ----------------1
(am) x (an) = am + n-------------------2
am ÷ an = am ? n----------------3
and if pX = pY then X will be equal to Y. means X = Y;----------------4
⇒ ( 32n x 32 x 3n - 33n ) / ( 33m x 23 ) = 1/27
Solve the equation.Correct Option: A
( 9n x 32 x (3-n/2)-2 - (27)n ) / ( 33m x 23 ) = 1/27
⇒ ( 32n x 32 x 3n - 33n) / ( 33m x 23 ) = 1/27
⇒ ( 32n + n x 32 - 33n) / ( 33m x 23 )= 1/27
⇒ ( 33n x 32 - 33n) / ( 33m x 23 ) = 1/27
⇒ 33n( 32 - 1) / ( 33m x 8 ) = 1/27
⇒ 33n( 9 - 1) / (33m x 8 ) = 1/27
⇒ ( 33n x 8 ) / (33m x 8 ) = 1/27
⇒ 33n / 33m = 1/27
⇒ 33n - 3m = 1/33
⇒ 33( n - m ) = 3-3
3(n - m) = -3
or n - m = -1
or m - n = 1
- If x = √3 + 1/ √3 - 1 and y = √3 - 1/ √3 + 1, then x2 + y2 is equal to
-
View Hint View Answer Discuss in Forum
You can square the both the equation and add them to find the answer.
x2 + y2 = ( (√3 + 1 ) / ( √3 - 1 ) )2 + ( (√3 - 1 ) / (√3 + 1) )2
x2 + y2 = ( √3 + 1 )2 / ( √3 - 1 ) 2 + (√3 - 1 )2 / (√3 + 1) 2
Solve further by applying the Law of Algebra formulaCorrect Option: A
You can square the both the equation and add them to find the answer.
x2 + y2 = ( (√3 + 1 ) / ( √3 - 1 ) )2 + ( (√3 - 1 ) / (√3 + 1) )2
x2 + y2 = ( √3 + 1 )2 / ( √3 - 1 ) 2 + (√3 - 1 )2 / (√3 + 1) 2
x2 + y2 = ( ( 3 + 1 + 2 √3 ) / ( 3 + 1 - 2 √3 ) ) + ( ( 3 + 1 - 2√3) / ( 3 + 1 + 2 √3 ) )
x2 + y2 = ( 4 + 2 √3 ) / ( 4 - 2 √3 ) + ( 4 - 2√3 ) / ( 4 + 2 √3 )
x2 + y2 = ( 2 + √3 ) / ( 2 - √3 ) + ( 2 - √3 ) / ( 2 + √3 )
x2 + y2 = (4 + 3 + 4 √3 + 4 + 3 - 4 √3) / ( 4 - 3 )
x2 + y2 = 14
- Find the quotient when (a-1 - 1) is divided by (a - 1).
-
View Hint View Answer Discuss in Forum
Given equation is
a-1 - 1
Apply the law of Fractional Exponents and Laws of Exponents
x-y = 1/xy
Rationalize the above equation and divide as per given question and solve it.Correct Option: D
Given equation is
a-1 - 1
Apply the law of Fractional Exponents and Laws of Exponents
x-y = 1/xy
⇒ a-1 - 1 = 1/a - 1
⇒ a-1 - 1 = (1 - a)/a
Now divide by a - 1 in above equation,
⇒ ( a-1 - 1 ) ÷ (a - 1) = (1 - a)/a ÷ (a - 1)
⇒ ( a-1 - 1 ) ÷ (a - 1) = (1 - a)/a x 1/ (a - 1)
⇒ ( a-1 - 1 ) ÷ (a - 1) = -1x (a - 1)/a x 1/ (a - 1)
⇒ ( a-1 - 1 ) ÷ (a - 1) = -1/a
∴ Required quotient = -1/a.
- If 16 x 8n + 2 = 2m, then m is equal to
-
View Hint View Answer Discuss in Forum
Given that 16 x 8n + 2 = 2m
Apply the law of Fractional Exponents and Laws of Exponents
if a multiply three times a x a x a then
a x a x a = a3
if a multiply two times a x a then
a x a = a2
if a multiply n times a x a x a x....up to n times, then
a x a x a x a ......up to n times = an
and if pX = pY then X will be equal to Y. means X = Y;
Law of exponent
aman = am+nCorrect Option: D
Given that 16 x 8n + 2 = 2m
Apply the law of Fractional Exponents and Laws of Exponents
if a multiply three times a x a x a then
a x a x a = a3
if a multiply two times a x a then
a x a = a2
if a multiply n times a x a x a x....up to n times, then
a x a x a x a ......up to n times = an
⇒ (2)4 x 23 x (n+2) = 2m
⇒ (2)4 x 23n+6 = 2m
aman = am+n
⇒ (2)(4 + 3n + 6) = 2m
⇒ (2)(3n + 10) = 2m
if pX = pY then X will be equal to Y. means X = Y;
On comparing, we get
3n + 10 = m
⇒ m = 3n + 10;